Acitretin-Conjugated Dextran Nanoparticles Ameliorate Psoriasis-like Skin Disease at Low Dosages - Lan, Jiajia; Li, Yuce; Wen, Jingjing; Chen, Yu; Yang, Jing; Zhao, Liang; Xia, Yuting; Du, Hongyao; Tao, Juan; Li, Yan; Zhu, Jintao (Frontiers in Bioengineering and Biotechnology, 2022)
Psoriasis is a common chronic inflammatory skin disease mainly characterized by keratinocyte hyperproliferation and massive infiltration of inflammatory immune cells. Acitretin (ACT), an FDA-approved first-line systemic drug for psoriasis treatment, could suppress the proliferation of keratinocytes and downregulate the expression of inflammatory cytokines by modulating signal transducer and activator of transcription (STAT) signaling pathways. However, dose-dependent side effects of ACT limit its long-term administration in the clinic. Therefore, improving the therapeutic efficacy of ACT to reduce clinical dosage will benefit the patients. Here, we develop ACT-conjugated dextran nanoparticles (ACT-Dex NPs) and evaluated the potential for psoriasis treatment. Our results indicate that ACT-Dex NPs ameliorate psoriasis-like skin disease significantly at a low dosage which does not cause side effects, while neat ACT drugs at an equivalent dosage provide much less benefit. Moreover, we demonstrate that ACT-Dex NPs suppress keratinocyte proliferation more efficiently than neat ACT by enhancing the inhibitory effect on STAT3 phosphorylation. Thus, the proposed ACT-Dex NPs provide an effective and safe option for psoriasis treatment.